State-driven architecture design for safety-critical software product lines - Ebnauf, Mozamil; Abdelmoez, W.; Ammar, Hany H.; Hassan Abdalla Hashim, Aisha; Abdelhamid, Mohamed (IEEE, 2020)
The safety is considered one of the most critical issues in the design of cyber-physical systems (CPS). The Software Product-Line (SPL) and reusable software components are suitable approaches for CPS, which are often re-engineered from existing systems. Currently, the influence of architecture in assurance of software safety is being increasingly recognized. However, the safety-based architectural design methods are limited in SPLs because of the complexity and variabilities existing in SPL architectures. A new statechart-based safety pattern and adaptation of our previous SPL Architecture design method are presented in this paper. Also the paper describes a simplified safety assessment model which is used to evaluate the safety improvement in the design of the SPLA after using the proposed safety design pattern. Finally, to illustrate the effect of the design pattern in the PLA design, a simplified automated Electromechanical Braking System (EBS) product line is used as a running example. The results show that there is a considerable improvement in the system safety design after using the proposed safety pattern.